Minority politics of Bengal muslims in late colonial era and their understanding of Pakistan - Joy, Shafiul Aziz (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2018.